2015
DOI: 10.1002/hep.27571
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic adenosine monophosphate–responsive element modulator alpha overexpression impairs function of hepatic myeloid‐derived suppressor cells and aggravates immune‐mediated hepatitis in mice

Abstract: Molecular factors driving immune-mediated inflammation in the liver are incompletely understood. The transcription factor, cyclic adenosine monophosphate-responsive element modulator alpha (CREMa) can endorse differentiation of T lymphocytes toward T-helper (Th)17 cells, thereby promoting autoimmunity in systemic lupus erythematosus or lung inflammation. To investigate the role of CREMa in liver disease, we subjected transgenic (Tg) mice overexpressing CREMa under control of the CD2 promoter (crem tg mice), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Our data demonstrate an increase of CD11b + CD33 + HLA-DR −/lo MDSCs and the receptor RANK in the periphery of IgG4-SC. This is consistent with other reports in immune-mediated diseases (12,40,41) that in response to chronic stimulation MDSC expansion was initiated and converted into immune-suppressive cells. RANKL induces the expansion and suppressive activity of MDSCs through interacting with RANK and activating the NF-κB pathway.…”
Section: Discussionsupporting
confidence: 93%
“…Our data demonstrate an increase of CD11b + CD33 + HLA-DR −/lo MDSCs and the receptor RANK in the periphery of IgG4-SC. This is consistent with other reports in immune-mediated diseases (12,40,41) that in response to chronic stimulation MDSC expansion was initiated and converted into immune-suppressive cells. RANKL induces the expansion and suppressive activity of MDSCs through interacting with RANK and activating the NF-κB pathway.…”
Section: Discussionsupporting
confidence: 93%
“…Since we observed major differences in the effect of CREMα Tg T cells on the Nemo Δhepa phenotype, associated with their differentiation pattern, 17 we further investigated the Th17 phenotype in hepatic T cells ( figure 6 B). Indeed, our FACS analysis revealed that CREMα Tg control mice showed no increase in Rorγt + T cells in the liver.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of CREMα under control of the CD2 promoter in mice has been shown to reduce the number and alter the composition of immune cells in the liver. 17 Previous work in our laboratory 34 has shown the beneficial effects of depleting NK and NKT cells in Nemo Δhepa mice. In the same line of results, Nemo Δhepa /CREMα Tg animals display reduced amounts of NKT cells, and of proinflammatory macrophages, granulocytes, CD11b + DCs and CD8 + T cells, suggesting an overall reduced inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Small intestine, blood, bone marrow, and spleen cells were subjected to red blood cell lysis using Pharm Lyse (BD Biosciences, San Jose, USA). Flow cytometric analysis was done as described in detail before (79). Antibodies were purchased from eBioscience (CD45, CD11b, Ly6G, F4/80, CD3, CD4, CD8, CD103, and NK1.1), BD Biosciences (Gr1, I-A b ), and Biolegend (CD11c).…”
Section: Flow Cytometric Analyses Of Murine Leukocyte Populationsmentioning
confidence: 99%